The Use of Songs as A Learning Medium in Christian Religious Education at Elementary Schools in Kalimantan Tengah - Lukas, Lukas; Wijaya, Nicolhas Jurdy (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Learning media play a vital role in creating engaging and effective learning experiences. Among the various media used in education, songs serve as an appealing audio medium that helps students learn through enjoyment and emotion. This study aims to describe the use of songs as a learning medium in Christian Religious Education (CRE) at Hurung 1 Public Elementary School, Pulang Pisau Regency, Kalimantan Tengah. Using a qualitative descriptive method, data were collected through observation, interviews, and document analysis. The findings show that songs are used at three stages of the learning process: at the beginning to build interest and connect with the topic, in the middle as a learning resource to deepen understanding, and at the end as a reflection tool to strengthen moral and spiritual values. The use of songs enhances students’ enthusiasm, focus, and comprehension, while also assisting teachers in delivering Christian values effectively. In conclusion, songs serve as an effective pedagogical medium that integrates emotional, cognitive, and spiritual dimensions in Christian Religious Education.